On the need to plan for increased logistical challenges in ecological projects due to impacts of a changing climate. (15th April 2023) - Thomson, Hanna M.; Gerwing, Travis G.
Abstract: Anthropogenic climate change is manifesting in more extreme and unpredictable weather. We posit that weather-dependent biological fieldwork, especially in marine and coastal settings, is increasingly hindered by manifestations of a changing climate. Even if field researchers and practitioners can safely withstand the elements, research and monitoring protocols commonly dictate suitable conditions for data collection. Subsequently, climate change restricts field researchers' ability to collect data on ecological systems impacted by the changing climate. Research projects and protocols require active reconfiguration to future-proof field data collection. We suggest that weather-induced hurdles currently pressuring the execution of field campaigns can be mitigated by (1) conducting a cost-benefit analysis of existing research projects to streamline the use of limited resources, (2) adopting emerging technologies to reduce time in the field, and (3) collaborating with organizations and community-based scientists to increase project efficiency. Highlights: Climate change-induced extreme weather is increasingly impacting the success of field campaigns. Proactive assessment and redesign of research and monitoring projects are needed to future-proof data collection. Mitigation of fieldwork hurdles can include cost-benefit analyses, incorporation of emerging technologies, and enhanced collaboration.